Synthesis, Structure, and Reactivity of a Magnesium(0) Complex with a Polarized Mgδ−─Caδ+ Bond - Thakur, Sandeep Kumar; Langer, Jens; Roig, Nil; Patro, A Ganesh; Schmidt, Marcel; Alonso, Mercedes; Harder, Sjoerd (Angewandte Chemie International Edition, 2026)
Despite numerous examples of Mg─Mg bound complexes, complexes with unsupported two-center-two-electron Mg─Ca bonds so far always eluded their isolation. This is due to Mgδ¯-Caδ+ polarization and their inherently very high reactivity resulting in oxidative addition to C─H bonds in either the ligand or solvent. Using a combination of bulky β-diketiminate (BDI*) and amidinate (Am*) ligands, we now present (BDI*)Mg-Ca(Am*); BDI* = HC[C(tBu)N(DIPeP)]2, DIPeP = 2,6-Et2C-phenyl; Am* = tBuC(N-DIPP)2, DIPP = 2,6-iPr-phenyl. The crystal structure shows a Mg─Ca bond of 3.298 Å and Mg/Ca NPA charges of +0.66/+1.28. This reflects considerable Mgδ¯-Caδ+ polarization and is in line with the formal oxidation states Mg0-CaII. Effective-Oxidation-State (EOS) analysis confirms these formal oxidation states, but a low reliability index of 69.8% indicates that these are not fully representative for the electron distribution. Atoms-In-Molecules (AIM) shows a bond-critical-point on the Mg–Ca axis but a non-nuclear-attractor (NNA) was not observed. EDA-NOCV using two different fragmentations, (BDI*)Mgˉ/(Am*)Ca+ or (BDI*)Mg●/(Am*)Ca●, shows that the complex is best described as a combination of neutral radicals. The Mg0–CaII/MgI–CaI ambiguity results in a highly reactive Mgδ¯─Caδ+ bond. This is confirmed by its reaction with CyN═C═NCy and Ph2C═CH2 showing the electrophilic nature of Ca and nucleophilic reactivity for Mg.
CRIS-Team Scopus Importer:2026-01-26
Keywords: Calcium; DFT; Low-valent; Magnesium; Metal–metal bonding